IL-33 drives the antitumour effects of dendritic cells via upregulating CYLD expression in pulmonary adenocarcinoma. Issue 1 (4th December 2019) - Zhang, Jiguang; Chen, Yangming; Chen, Kai; Huang, Yunchao; Xu, Xunyu; Chen, Qianshun; Huang, Chen; Luo, Jiewei; Lin, Xing
Abstract: Lung adenocarcinoma is one of the leading causes of cancer-related death worldwide. Low expression of Interleukin-33 (IL-33) was reported to be associated with the progression of pulmonary adenocarcinoma. However, the IL-33-mediated immunoregulation in pulmonary adenocarcinoma remains unclear. In this study, we found that IL-33 treatment evidently repressed tumour growth, induced CD4 + T cells infiltration and IL-17 expression in pulmonary adenocarcinoma. Notably, IL-33 treatment increased the number of Dendritic Cells (DCs) in pulmonary adenocarcinoma. More importantly, IL-33 induced maturation and regulated the function of DCs by increasing expression of DCs mature markers (CD40 and CD80, CD86) DCs-function-related gene including antigen presentation genes ( HLA-DMA, HLA-DMB and CD74 ) and cytokines (IL-1β, IL-6 and TNF). Mechanistic studies demonstrated that IL-33 treatment induced DCs maturation by upregulating CYLD expression in DCs. In addition, CYLD played an important role in DCs-induced T cell proliferation and IL-17 secretion. In conclusion, our study demonstrated that IL-33 mediated immunoregulation in pulmonary adenocarcinoma by improving DC-induced T cell proliferation by upregulating CYLD expression.